Terrorism in the United Kingdom and United States of America, 1998-2019 - Ross, Vien-Michael (2019)
Terrorism is an inevitable result of the conflicting politics, beliefs and values in the modern world; however the characteristics of attacks differ. The current study aimed to establish what characteristics were present in terrorist attacks occurring in the United States of America and the United Kingdom between 1998-2019. Features of both the offender and the offence were recorded and analysed. Possible differences between attacks in the two nations were also explored. A media analysis design was conducted to assess 83 terrorist attacks satisfying inclusion criteria. Data were assimilated and analysed predominantly using logistic regression. Results illustrated several significant findings, primarily that the method of attack, frequency of firearm usage and location of attack significantly differed between the USA and UK. These countries should therefore be considered independently when researching terrorism. Implications for possible typology generation and suggestions for future research are discussed.